Characterizing real world safety profile of oral Janus kinase inhibitors among adult atopic dermatitis patients: evidence transporting from the rheumatoid arthritis population. (3rd August 2022) - Montez-Rath, Maria E.; Lubwama, Robert; Kapphahn, Kris; Ling, Albee Y.; LoCasale, Robert; Robinson, Lacey; Chandross, Karen J.; Desai, Manisha
Abstract: Objective: To address potential safety concerns of Janus Kinase Inhibitors (JAK-Is), we characterized their safety profile in the atopic dermatitis (AD) patient population. Methods: In this retrospective observational study, we used propensity score-based methods and a Poisson modeling framework to estimate the incidence of health outcomes of interest (HOI) for the AD patient. To that end, two mutually exclusive cohorts were created using a real world data resource: a rheumatoid arthritis (RA) cohort, where we directly quantify the safety risk of JAK-Is on HOIs, and an AD cohort, that comprises the target population of interest and to whom we transport the results obtained from the RA cohort. The RA cohort included all adults who filled at least one prescription for a JAK-I (tofacitinib, baricitinib, or upadacitinib) between 1 January 2017 and 31 January 2020. The AD cohort consisted of all adults diagnosed with AD during the same period. We first estimated the incidence rate of each HOI in the RA cohort, and then transported the results to the AD population. Results: The RA and AD cohorts included 5, 296 and 261, 855 patients, respectively. On average, patients in the AD cohort were younger, more often male, more likely to be Asian, and had higher household income. They also had a lower prevalence of several comorbid conditions including hypertension, chronic kidney disease, obesity, and depression. Overall, the transported incidence rates of the HOIs to the AD cohort were lower than those obtained in the RA cohort by 13–50%. Conclusion: We applied transportability methods to characterize the risk of the HOIs in the AD population and found absolute risks higher than that of the general population. Future work is needed to validate these conclusions in comparable populations.